MOTIVATION IN MANAGEMENT - Erkin To’rayev Eshkabilovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article explores the concept of motivation in management and its impact on employee performance and organizational success. By examining different motivational theories, methods, and their outcomes, we gain insights into how managers can effectively motivate their employees to achieve higher levels of productivity and engagement. The article concludes with suggestions for implementing motivational strategies in the workplace.